What Benefits Might a Family Expect From Using Spiritual Coping Mechanisms When Providing Care for People With Schizophrenia? Literature Review - Faizatur Rohmi SKep, Ns, MKep; Ah Yusuf SKp, MKes; Rizky Fitriasari PK, SKep, Ns, MKep; Hardiyanto Agustinus SKep, Ns, MKep (SAGE Publishing, 2023)
Introduction Caring for people with schizophrenia has consequences, one of which is stressors during care. Families as caregivers often using coping strategies that involve relationships with self, others, or the transcendent/God or nature and also may include religious/spiritual practices. Objectives This literature review aims to identify the benefit of using spiritual coping as used by a family schizophrenia caregiver. The variable is spiritual coping. Methods This literature review method used PRISMA methodology for systematic reviews. Search was conducted in March 2017, updated in August 2022 and submitted in April 2023 for the publication process, limited to English by using electronic databases: Scopus, ScienceDirect, Sage, ProQuest, and PubMed. Results Fifteen studies were included in this review. Two synthesized findings emerged: spiritual coping strategies used by family caregivers give positive effects for family. Conclusion When the stress or crisis phase is experienced while caring for people with schizophrenia, the family who acts as a caregiver reveals the meaning of life they have and that they feel hopelessness and helplessness. In an effort to overcome the family's burden as caregivers, they often use spiritual coping, which is important to increase the caregiver's wellbeing.